Adaptation and job satisfaction: empirical research, generalizations and results - O. V. Makeeva (Библиосфера)
Studying adaptation and job satisfaction is one of the most important problems in modern management. Domestic sociologists and psychologists have been actively engaged in research of this topic since 1960s, foreign researchers - since the early XX century. Job satisfaction is often regarded as adaptation results measured with objective and subjective indicators. The most recognized factors influencing it are the following: gender, age, experience, work character and content, profession prestige in society, personal value-meaning orientations of employees. This theme is poorly developed in library science, there is practically no deep theoretical research. In 2014 SPSTL SB RAS carried on a study of adaptation and job satisfaction in three large libraries of the Siberian Federal District. General (common for all libraries) and particular results were obtained.